Analysis of the values of national defense and social responsibility in the implementation of work safety culture in MSMEs in Medan City - Istifani Nasution; Wasiyem Wasiyem (Jurnal Riset Ilmu Pendidikan, 2026)
MSMEs play a strategic role in the national economy, but the implementation of occupational safety culture remains relatively low, especially in the informal sector. This study aims to analyze the internalization of national defense values ??and social responsibility in the implementation of occupational safety culture in MSMEs in Medan City. The study used a qualitative approach with a case study design through in-depth interviews with three informants: MSME owners, workers, and MSME assistants, supported by field observations and documentation. The results show that national defense values ??are interpreted as honest work behavior, discipline, compliance with obligations, and contribution to the local economy. These values ??encourage the growth of social responsibility in the form of above-standard wages, assistance with worker medical expenses, and responsible business waste management. However, the occupational safety culture has not been formally institutionalized, marked by the absence of OSH Standard Operating Procedures (SOPs), limited use of Personal Protective Equipment (PPE), minimal OSH training, and rudimentary emergency response procedures. This study confirms that the values ??of national defense and social responsibility are social capital that can support the strengthening of occupational safety culture, but require structural intervention through coaching, training, and standardization of OHS practices in MSMEs.